Liver Function Test in Cholestasis - Kompiang Gautama; Anki Tri Rini; Sudaryati S. (Paediatrica Indonesiana, 1995)
Cholestasis is impaired bile flow that cause prolonged evacuation of conjugated bilirubin and other substances which are dependent of bile flow for its excretion. The liver function test is useful to determine the severity of disease, to follow up its progress, and to predict the prognosis. This study was performed restropectively from the medical record of cholestatic patients who were admitted to the Department of Child Health, Central Hospital of Denpasar, from January 1992 to December 1993. Among 34 patients with cholestasis, 27 (19 intrahepatic and 8 extrahepatic cholestasis) were included in this study. Although the means of transaminase enzymes (SGOT, SGPT) in intrahepatic cholestasis were higher significantly than those in extrahepatic cholestasis, the increase of these enzymes five times or more than normal was not different significantly. The means of GGT and alkaline phospatase (AP) in extrahepatic groups were higher significantly than those in intrahepatic groups, and the increase of GGT more five times than normal was dilferent significantly as well. The means of total and conjugated bilirubin levels were higher in .extrahepatic group, but were not dilferent significantly.